2021
DOI: 10.1177/09721509211001511
|View full text |Cite
|
Sign up to set email alerts
|

How do Stock Market Participants Value ESG Performance? Evidence from Middle Eastern and North African Countries

Abstract: Empirical evidence indicates that Environmental, Social, and Governance (ESG) practices are associated with firm financial performance, but little is known about stock market participants’ behaviour towards ESG practices, especially in unfavourable settings, where the level of shareholders’ protection is relatively weak. In this article, we examine whether ESG performance provides shareholders with value-relevant information to help them in their equity pricing decisions. Using a cross-country sample of non-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 83 publications
3
26
0
1
Order By: Relevance
“…Studies such as Lee and Yeo (2016), Zhou et al (2017) and Carè and Forgione (2019) showed that ESG reporting had a positive impact on the financial performance of firms. Some streams of literature, such as those of Carnevale et al (2009), Sharma et al (2019) and Al-Hiyari and Kolsi (2021), also demonstrated that ESG reporting hurts the performance of firms. The argument advanced by these studies is that ESG reporting consumes resources that exceed the benefits obtained from such practices.…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Studies such as Lee and Yeo (2016), Zhou et al (2017) and Carè and Forgione (2019) showed that ESG reporting had a positive impact on the financial performance of firms. Some streams of literature, such as those of Carnevale et al (2009), Sharma et al (2019) and Al-Hiyari and Kolsi (2021), also demonstrated that ESG reporting hurts the performance of firms. The argument advanced by these studies is that ESG reporting consumes resources that exceed the benefits obtained from such practices.…”
Section: Empirical Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The first stream of literature our article contributes to is the previous studies on the relationship between sustainability and a broad spectrum of variables accounting for firm performance (Al-Hiyari & Kolsi, 2021). This set of studies covering ESG and financial performance strives to explain findings by relating them to several social science theories, like the stakeholder theory (Freeman, 1984) and the signalling theory (Healy & Palepu, 2001; Spence, 1973).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Fatemi et al (2018) demonstrate that ESG performance affects the firm’s value; ESG strength positively impacts firm’s value whereas ESG weaknesses negatively impacts the firm’s value. Al-Hiyari and Kolsi (2021) states that investors and participants in the market consider the ESG performance when determining the firm’s value. A similar study conducted by Wong et al (2021) on Malaysian firms confirms that ESG certification lowers the firms’ cost of capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies show that stakeholders are increasingly interested in non-financial disclosures on environment, social and governance (ESG) (Al-Hiyari & Kolsi, 2021; Khan et al, 2016). Many opportunities and challenges have emerged for firms with their shareholders regarding risk-return relationships.…”
Section: Introductionmentioning
confidence: 99%